Recurrent thrombosis despite anticoagulation in a man with monocytosis - Bösiger, J.; Biasiutti, F. Demarmels (Hämostaseologie, 2003)
Recurrent thromboembolism despite oral anticoagulation is primarily suspicious of overt or occult neoplasia. We report on a man (age: 67 years) who presented with severe thrombophilia which was only controlled when the patient was set on a combined anticoagulation with low molecular weight heparin in supratherapeutic dosage and phenprocoumon with a target INR of 2.0. Despite repeated evaluation over about two years, a malignant tumour could never be demonstrated. However, the patient suffered in addition to a protein S deficiency from an antiphosphospholipid syndrome and a chronic myelomonocytic leukaemia.We postulate that the accepted strong thrombogenicity of antiphosphospholipid syndrome was further increased by protein S deficiency and a possibly procoagulatory effect of the abnormal monocytes explaining the severe thrombophilia resistant to standard therapeutic anticoagulation with a vitamin K antagonist and usual therapeutic doses of low molecular weight heparin, respectively.
Keywords: Thrombosis; monocytosis; anticoagulation